Combating Neonatal Mortality in Rural Haiti—Early Assessment of "Helping Babies Breathe" in a Community Setting [27Q]. (May 2016) - Buresh, Chris; Ryan, Ginny; Foley, Caitlin; Valukas, Cassie; Kompare, Michelle
Abstract : INTRODUCTION: Community Health Initiative Haiti (CHI), a non-profit organization working in rural Haiti, has witnessed high rates of infant mortality. In response, CHI adopted the Helping Babies Breathe (HBB) peer-to-peer neonatal resuscitation curriculum plus education on breast feeding and post-partum contraception. METHODS: CHI-employed Community Health Workers (CHWs) train in HBB, identify pregnant women (68% deliver at home) through house visits and rural clinics and then provide 3 trainings to the lay midwife, relative or neighbor who will attend the delivery. The pregnant woman also receives a home "birthing kit" to demonstrate HBB principles. Outcomes are gathered by CHWs at a post-partum visit. We compared HBB outcomes with those of a group of community women who did not participate. RESULTS: 53 pregnant women have enrolled in HBB; 37 of these women have delivered 40 babies. Of enrollees, 51/53 (96%) of their birth attendants had at least 1 training session and 20 (38%) had all 3 sessions. 17/37 mothers who delivered (46%) felt HBB was very helpful and 11 (30%) were interested in further training/training others. 1/40 HBB babies (2.5%) died and 4/40 (10%) were "sick, " compared to 1/23 (4%) non-participant babies who died and 4/23 (17%) who were sick. All HBB and non-participant mothers were alive; 2/37 HBB mothers (5.4%) were "sick" compared to 5/20 (25%) of non-participant mothers who were "sick." CONCLUSION: A simple, community-based neonatal resuscitation program plus post-partum education for attendants of home deliveries in rural Haiti is well-received and may effectively reduce maternal and neonatal morbidity and mortality.